Feasibility Study Designing Electric Motorcycles With Fossil Fuels Compared To Hybrid Systems On 150Cc Motorcycles - Pawenary, Pawenary; Azzahra, Septianissa; Azis, Hastuti; Prabuwono, Anton Satria (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
In this study, an electric vehicle was designed using fossil fuels compared to the hybrid system on a 150cc motorcycle. The design of electric motorcycle vehicles is focused to know the feasibility study comparison between engine drive and electrical drive. In the design of electric motorcycle vehicles know how to make technical economic calculations on electric motorcycles. And converting energy from mechanical energy into electric energy or vice versa requires a device called an electric motor. Having the knowledge and experience in the manufacture of electric motors will be more useful and become important in the future. Electric vehicles are the solution to the problem of depleting petroleum reserves and pollution problems that increase each year due to exhaust emissions produced by oil-fueled vehicles. contribution of motor vehicle exhaust as a source of air pollutionreaches 60-70%. The decline of fossil fuels in the world is also a major problem that is currently unresolved. The analytical technique used in this study is a descriptive statistic technique. Where in this study will be carried out an assessment of the technical data that occurs on the calculation of the speed of what motor is in accordance with the specified standards.